2019
DOI: 10.18823/asiatefl.2019.16.4.3.1103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Peer Feedback on Learning : A Case of EFL Teacher Trainees

Abstract: The present study investigated the learners" perceived impact of peer feedback on their learning after one semester"s practicing it in a content course classroom, with additional interests in the influence of personal characteristics in the shaping of their perception and factors underlying their approaches to peer-feedback activities. Participants were 52 Korean college students majoring in TEFL.A survey was administered at the beginning and the end of the semester in search of any possible change in their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Regarding individual differences and assessment experience, two different studies showed that perceptions of peer feedback changed as students got more experience with it. Joh (2019) found that for a sample of Korean college students, extroverts expected to get more from peer feedback than did introverts, but after experiencing peer feedback, these differences disappeared and positive perceptions developed. Ghahari and Sedaghat (2018) similarly found that college students' desire for peer comments on their writing grew as they experienced peer feedback, and that feelings of jealousy and resentment toward peers gradually decreased as desire to make progress in their writing increased with experience.…”
Section: Support For Claimmentioning
confidence: 93%
“…Regarding individual differences and assessment experience, two different studies showed that perceptions of peer feedback changed as students got more experience with it. Joh (2019) found that for a sample of Korean college students, extroverts expected to get more from peer feedback than did introverts, but after experiencing peer feedback, these differences disappeared and positive perceptions developed. Ghahari and Sedaghat (2018) similarly found that college students' desire for peer comments on their writing grew as they experienced peer feedback, and that feelings of jealousy and resentment toward peers gradually decreased as desire to make progress in their writing increased with experience.…”
Section: Support For Claimmentioning
confidence: 93%
“…The literature review shows that a large number of studies have been conducted to examine teacher feedback (e.g. Azizi et al, 2020;García & Martínez, 2018;González, 2010;Hoomanfard & Rahimi, 2020;Jabbari et al, 2017;Joh, 2019;Sung, 2021;Waluyo & Rofiah, 2021) and peer feedback (Hoomanfard & Rahimi, 2021;Huisman et al, 2018;Latifi et al, 2021;Wu & Schunn, 2021) in both second and foreign language learning context although little is known about the discrepancies between written synchronous and asynchronous peer feedback. Thus, the subsequent research questions led this research:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although previous studies (Abuseileek & Abualsha'r, 2012;Azizi et al, 2020;García & Martínez, 2018;González, 2010;Jabbari et al, 2017;Joh, 2019;Song & Usaha, 2009;Storch, 2017;Sung, 2021;Waluyo & Rofiah, 2021) have briefly pointed at this issue, no plenary study examined the way synchronous and asynchronous peer feedback types are capable of developing the quality of IELTS candidates' writing. One more gap in the literature which the present study endeavors to cover is related to the effect of synchronous and asynchronous peer feedback on students' use of language function.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of peer correction was also proven by Joh (2019). Fifty two Korean college students majoring in TEFL were studied at the beginning and the end of the semester with the purpose of identifying the possible change of their perception after practicing of peer feedback activities.…”
Section: Observation Of Teaching Demonstrationmentioning
confidence: 99%